Reducing asthma exacerbations in vulnerable children through a medical–legal partnership. (1st February 2023) - Mainardi, Anne S.; Harris, Drew; Rosenthal, Alice; Redlich, Carrie A.; Hu, Buqu; Fenick, Ada M.
Abstract: Background: Asthma health disparities are widely recognized, with worse outcomes in children from low income families. In a Medical-Legal Partnership (MLP), an attorney is embedded in a healthcare setting to address social determinants of health. We studied whether an MLP could impact asthma exacerbation rates in a vulnerable urban population at an academic children's hospital. Methods: The study population comprised children with asthma who were referred to the MLP between 2013 and 2017. We compared healthcare utilization for asthma exacerbations managed in primary care, emergency department and inpatient settings in the year before and year after MLP intervention. Results: 98 children with asthma were included in the study. The mean total encounters per person per year decreased from 1.16 to 0.66 (relative reduction 44.2%, p  < 0.01). The largest effect was on hospitalizations, with a reduction from 0.33 to 0.10 hospitalizations per patient per year (relative reduction 69.7%, p  < 0.01). Encounters for asthma exacerbations in the primary care office and emergency department also decreased but these changes did not meet statistical significance. Conclusion: In a pediatric population with asthma, an MLP intervention was associated with a significant reduction in asthma exacerbation encounters and hospitalizations comparing the year before and after MLP intervention. Further studies are needed to better understand which interventions are most effective, and for which patient groups MLP referral would be particularly useful. MLPs may be an important way to reduce health disparities in patients with asthma and other chronic illnesses. KEYWORDS: Management/control; pediatrics